A comparative study on fatigue indicator parameters for near‐α titanium alloys. Issue 1 (10th October 2022) - Liu, Yang; Zhang, Xiang; Oskay, Caglar
Abstract: Nucleation of in‐service cracks leads to detrimental consequences for structural components of near‐ α titanium alloys subjected to fatigue loads. Experimental observations show that the fatigue initiation facets usually form in certain crystallographic orientation ranges of "hard" primary α grains which differ between pure and dwell fatigue loads. In this manuscript, a comparative study has been performed using several fatigue indicator parameters (FIPs) to assess their ability to predict the location of fatigue crack nucleation in near‐ α titanium alloy microstructures. All selected FIPs are implemented within the same polycrystalline plasticity finite element modeling framework to facilitate one‐to‐one comparisons. Comparison on predictability of critical initiation locations and their crystallographic orientations is studied for incorporated FIPs under pure and dwell fatigue. The critical locations predicted by some FIPs were found to be close to each other, and consistent with the crystallographic orientation ranges from fractography measurements, in addition to the range transition from pure to dwell fatigue loads. Critical locations from slip driven FIPs are obtained to be several grains away from that of the former ones and are inclined to capture orientations of slip traces from experiments. Highlights: Comparative study of is performed on different fatigue indicator parameters in the same CPFE framework. Some FIPs show similar critical sites and crystallography thereof, consistent with experimental data. CP results of these FIPs capture the experimental orientation range transition of critical sites from pure to dwell fatigue load. Proposed FIP, solely based on dislocation density, is validated through comparison with other FIPs and experiments.